Hydrothermal synthesis of zeolite Y from green materials. (25th February 2021) - Dasgupta, Sudipta; Klunk, Marcos Antônio; Das, Mohuli; Xavier, Soyane Juceli Siqueira; Chemale, Farid; Wander, Paulo Roberto; Moraes, Carlos Alberto Mendes
Abstract: Several probes have been conducted by the scientific community to reduce emissions of greenhouse gases such as carbon dioxide (CO2 ). A zeolitic material is capable of CO2 adsorption with the aid of such technologies. Our present work is to efficiently synthesize zeolite Y with four Si/Al ratios (2.0, 2.5, 3.0, and 3.5) from green materials such as rice husk ash (source of Si) and metakaolin (source of Al). The method for preparing zeolite Y involves hydrothermal synthesis in a hydrodynamic reactor at 120°C temperature, for a reaction time of 24 hours. These synthetic zeolites represent high values for surface area as well as pore volume in micropore range and are compatible with the size of CO2 molecules. The zeolite Y (with Si/Al ratio 3.5) has an absorption capacity of 3.35 mmol CO2 /g at (900 kPa) pressure, thereby demonstrating high efficiency for CO2 adsorption. The spectra of FTIR indicate Si‐OH‐Al groups, while the vibrations corresponding to Si‐O‐Si or Si‐O‐Al compounds display the characteristic structure of zeolite Y. Several tests have been conducted with the synthesized zeolites Y, which portrayed strong evidence of CO2 absorption abilities. Henceforth, it can be concluded that zeolites Y have significant potential for application in adsorption/desorption cycles of carbon dioxide. Abstract : Chemical reactions taking place inside the hydrodynamic reactor.